The wolf spider species from Peru and Bolivia described by Embrik Strand in 1908 (Araneae: Lycosidae: Lycosinae, Sosippinae, Allocosinae) - Brescovit, Antonio D.; Álvares, Éder S. S. (Zootaxa, 2011)
Five Lycosidae species from Peru and Bolivia described by Embrik Strand in 1908 are redescribed based on type specimens deposited in the Museum Wiesbaden, Wiesbaden and the Naturmuseum Senckenberg, Frankfurt. Hogna subaustralis (Strand) and H. yauliensis (Strand) remain in the genus Hogna and the male of H. subaustralis is described for the first time. Hogna rufimanoides (Strand) comb. nov., Hipasella arapensis (Strand) comb. nov. and Allocosa yurae (Strand) comb. nov. have all been transferred to other genera. New records from Peru were provided for all species.